2008
DOI: 10.2341/07-113
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Longevity of Restorations by Minimal Intervention: A Two-year Clinical Trial

Abstract: ©Operative Dentistry, 2008, 33-3, 258-264 G Moncada • E Fernández • J Martín C Arancibia • I Mjör • VV Gordan Clinical RelevanceTreating defective restorations with sealants, repair or refurbishing is an effective way to preserve and treat existing restorations. SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 8 publications
3
68
0
2
Order By: Relevance
“…One study by Gordon 28 used inappropriate randomisation of its participants and therefore resulted in its exclusion from the review. Moncada 40 and Moncada 39 reported on the same set of patients but at different follow up periods. In both of these studies the patients were reported to have been randomly allocated to treatment groups but the method of randomisation was not reported.…”
Section: Repair or Replacement Of Defective Restorations -The Evidencementioning
confidence: 91%
See 1 more Smart Citation
“…One study by Gordon 28 used inappropriate randomisation of its participants and therefore resulted in its exclusion from the review. Moncada 40 and Moncada 39 reported on the same set of patients but at different follow up periods. In both of these studies the patients were reported to have been randomly allocated to treatment groups but the method of randomisation was not reported.…”
Section: Repair or Replacement Of Defective Restorations -The Evidencementioning
confidence: 91%
“…The bibliographic references in these papers were also examined for other potentially eligible studies, but no further studies were identifi ed. Three of the remaining studies [39][40][41] were common to both resin composites and amalgam, whereas only one study 28 investigated composite resins.…”
Section: Repair or Replacement Of Defective Restorations -The Evidencementioning
confidence: 99%
“…It allows removal of localized defects with maximal preservation of tooth structure. Other advantages of repairs are minimal stress on the pulp, simplicity of technique provided access can be made and saving of time and material (1,(5)(6)(7)15). Total replacement is the most common treatment for amalgam restoration clinically diagnosed as defective (4).…”
Section: Discussionmentioning
confidence: 99%
“…Repair is an alternative option for treatment of defective amalgam restoration. It involves the removal of part of the restoration and any defective tissue adjacent to the defective area and restoration of the prepared site (6). This procedure allows preservation of sound tooth structure (7).…”
Section: Introductionmentioning
confidence: 99%
“…12 Developments in adhesive dentistry have provided clinicians with more options, helping them to restore teeth without destructive preparations and repair restorations rather than replacing them, minimising the loss of sound tooth tissue. 5,13,14 introDuCtion Continuing professional development (CPD) courses seek to inform, educate and develop practitioners' patterns of prescribing in line with the evidence base. This may include the introduction of new materials and methods or the modification of existing procedures.…”
mentioning
confidence: 99%